A study on the relationships between playfulness, physical self-efficacy, and school happiness among middle school students participating in “0th-period physical education class” in South Korea - Lee, Byungchan; Joung, Kihong; Jeon, Wonjae (Frontiers in Public Health, 2023)
The purpose of this study is to create a scientific basis for the establishment of "0th-period physical education class" activities in schools in the future, with the expectation that the associations of morning exercise can be activated in the Korean educational community. To achieve this goal, the present study aimed to determine the relationship between the playfulness experienced during the early morning exercise of middle school students and their physical self-efficacy and education for happiness. To examine the model, questionnaires were collected from 296 middle school students located in Seoul and Gyeonggi-do, South Korea. Correlation analysis and standard multiple regression analysis were performed to analyze the data using the SPSS 21.0. The findings were as follows: First, the playfulness of the middle school "0th-period physical education class" had a significant effect on physical self-efficacy. Second, playfulness had a significant effect on education for happiness. Thirdly, physical self-efficacy was found to have a significant effect on education for happiness. Based on the results of this study, we suggest that a "0th-period physical education class" with various activities should be held during the legally required time in South Korea.